Finance and Development, March 1966. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1966)
This paper analyzes how increasing population will impact the lives of people in the world in 2000. It underscores that in 2000, there will be more people, many living in crowded towns, suffering from even greater difficulties of transport and urban sprawl, both upward and outward. The provision of satisfactory housing for the mass of the population will be difficult, because, without subsidy, its construction would demand rentals equal at least to the occupant's annual income, while to subsidize so many tenants would be impossible.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet